Global eye health and the sustainable development goals: protocol for a scoping review. Issue 3 (18th March 2020) - Zhang, Justine H; Ramke, Jacqueline; Mwangi, Nyawira; Furtado, João; Yasmin, Sumrana; Bascaran, Covadonga; Ogundo, Cynthia; Jan, Catherine; Gordon, Iris; Congdon, Nathan; Burton, Matthew J
Abstract : Introduction: In 2015, most governments of the world committed to achieving 17 sustainable development goals (SDGs) by the year 2030. Efforts to improve eye health contribute to the advancement of several SDGs, including those not exclusively health-related. This scoping review will summarise the nature and extent of the published literature that demonstrates a link between improved eye health and advancement of the SDGs. Methods and analysis: Searches will be conducted in MEDLINE, Embase and Global Health for published, peer-reviewed manuscripts, with no time period, language or geographic limits. All intervention and observational studies will be included if they report a link between a change in eye health and (1) an outcome related to one of the SDGs or (2) an element on a pathway between eye health and an SDG (eg, productivity). Two investigators will independently screen titles and abstracts, followed by full-text screening of potentially relevant articles. Reference lists of all included articles will be examined to identify further potentially relevant studies. Conflicts between the two independent investigators will be discussed and resolved with a third investigator. For included articles, data regarding publication characteristics, study details and SDG-related outcomes will be extracted. Results will be synthesised by mapping the extracted data to a logic model, which will be refined through an iterative process during data synthesis. Ethics and dissemination: As this scoping review will only include published data, ethics approval will not be sought. The findings of the review will be published in an open-access, peer-reviewed journal. A summary of the results will be developed for website posting, stakeholder meetings and inclusion in the ongoing Lancet Global Health Commission on Global Eye Health.